Review of the flower-inhabiting water scavenger beetle genus Cycreon (Coleoptera, Hydrophilidae), with descriptions of new species and comments on its biology - Arriaga-Varela, Emmanuel; Wong, Sin Yeng; Kirejtshuk, Alexander G.; Fikáček, Martin (Pensoft on behalf of the Museum für Naturkunde, Leibniz Institute for Research on Evolution and Biodiversity at the Humboldt University Berlin., 2018)
The hydrophilid genus Cycreon Orchymont, 1919, previously known from two historical specimens only, is reviewed based on the numerous material collected recently from the inflorescences of various Araceae species in the Malay Peninsula and Borneo. Four species are recognized in the genus: C. sculpturatus Orchymont, 1919 from Sumatra, C. armandi Shatrovskiy, 2017 from Singapore, C. adolescens sp. n. from peninsular Malaysia, and C. floricola sp. n. with two subspecies, the nominotypical one from Peninsular Malaysia, and C. floricola borneanus subsp. n. from Borneo. All species are very similar, differing only by the pronotal punctation, shape of the clypeus and the mentum, and the form of the median lobe of the aedeagus. Specimens of C. floricola sp. n. and C. adolescens sp. n. were collected from inflorescences of various genera of the family Araceae. The field observations and analysis of mid gut contents indicates that they feed on organic material on internal organs of the inflorescences, including the pollen of the host plant. They were also observed to carry a large amount of pollen and are likely pollinators of their host species of Araceae.